Vitelly (Electrovibration Real Time Analyze): Innovation Utilizing Electro-vibration Technology and Artificial Intelligence for Texture Projection of Digital Selling Objects as an Effort to Prevent E-commerce Fraud in Indonesia - Nimas Nining Wardani; Moch. Aqilah Herdiansyah; Muhammad Maskur Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Vitelly is a concept of using electro-vibration technology in e-commerce applications that aims to reduce the number of e-commerce crimes in Indonesia. The public can experience the Vitelly concept by accessing e-commerce applications and can shop to their heart's content without worrying about e-commerce crimes. Vitelly's implementation method was initially carried out in a literature review and followed up with prototype design. The literature review process was carried out in May and the follow-up of the prototype assembly was carried out thereafter. From the various presentations that have been made, the results are obtained in the form of primary data on public opinion processed by the Wilcoxon test and secondary data from the literature review. In addition, the implications of implementing the Vitelly concept are synergizing several parties with the aim of strengthening and obtaining a lot of support for the development and application of the concept on an ongoing basis to reduce the number of e-commerce crimes in Indonesia.